Experiences of navigating anticipations and anxiety among patients having surgery for peripheral nerve tumours - Istefan, Emanuel; Giöstad, Alice; Carlsson, Ingela; Dahlin, Lars B. ; 0000-0003-1334-3099; Nyman, Erika (Scientific Reports, 2025)
Peripheral nerve tumours, most commonly schwannomas and neurofibromas, might present significant challenges by eliciting physical symptoms and emotional distress. We aimed to explore patients’ expectations, perceptions, and experiences regarding their diagnosis and the surgical treatment of a nerve tumour in the upper limb. Fourteen adults (10 women, 4 men; age range 35–85) from two Swedish hand surgery clinics participated in semi-structured interviews. Data saturation was reached. The interviews were transcribed verbatim and analysed following a conventional content analysis approach. Three main categories emerged. Causal Reasoning and Anticipations included explanatory thoughts of tumour aetiology, expectations of surgery, and concerns for the future. Anxiety and Adaptation comprised psychological strain, but also how to overcome challenges in daily life. Course of Care encompassed uncertainty and waiting time, interaction with health care and decision making on whether or not to have surgery. Recognising the interplay between physical symptoms and psychological responses underscores the need for personalised communication and patient-centred strategies, such as clear and empathetic information and shared decision-making, to reduce uncertainty and support individuals facing peripheral nerve tumours in the upper limb.
Keywords: Anxiety; Peripheral nervous system neoplasms; Surgery; Upper limb